Delusional Disorder Reflected in the Character of Jake in Charlie Kaufman’s I’m Thinking of Ending Things (2020) - Latifah Dwi Ariyani; Iis Istiqomah (Metaphor, 2021)
This study is aimed to analyze : (1) the type of delusion reflected in the main character reflected in Charlie Kaufman in “I’m Thinking of Ending Things”, (2) the psychological condition of Jake as delusion’s sufferer reflected in Charlie Kaufman in “I’m Thinking of Ending Things”. The study uses descriptive qualitative method to analyze the film entitled “I’m Thinking of Ending Things” directed by Charlie Kaufman as the objective research. The collecting data of the research method includes watching and reading, identifying, classifying, and selecting. The analyzing data of the research method by used displaying, explaining, and interpreting. The researcher analyzes the data by using Abnormal Psychology and Sigmund Freud Psychoanalysis. The result of the study : (1) the type of delusion reflected in the main character reflected in Charlie Kaufman in “I’m Thinking of Ending Things” such as erotomanic delusion and grandiose delusion; (2) the psychological condition of Jake as delusion’s sufferer in form of feeling anxious due to hallucination, delusion, and stress by using Sigmund Freud Psychoanalysis.